Estudo da eletrodeposição de ligas Fe-Ni-Mo e Fe-Ni-W com aplicações tecnológicas - Sanches, Luciana Schmidlin (Universidade Federal de São Carlos, 2008)
This paper reports a study on the electrodeposition of alloys Fe-Ni-Mo and Ni-Fe-W, the physical characterization and application in the reaction of hydrogen (RDH). The process of deposition and dissolution of alloys were studied by cyclical voltametric to determine the region of potential characteristic of the deposition and dissolution. The electrode used in the voltametric studies was platinum disc in solution of sodium citrate 0.2 mol / L at pH 5.0 and 8.0 on the grounds of concentration of ions Fe:Ni:Mo and Fe:Ni:W, 1:1:1, 1:10:1, 10:1:1, 10:10:1 and 10:10:2. The results of the voltametric analysis indicated the presence of well-defined peaks of dissolution for the alloy at high concentrations of Fe and Ni. Analysis of MEV, EDX, XPS and AA were used to characterize the alloys at pH 5.0 and 8.0. The morphology of materials containing Mo and W present the general structure globular, with the exception of alloy Fe-Ni-W obtained in the ratio 10:10:1 and pH 8 which is flat. Change occurs not linear in the size of a grain of these materials with the variation in the pH. These results of EDX indicated the presence of a smaller amount of oxygen in materials obtained in the base, and these were the deposits that had best results for RDH. The alloy with 80.6% Fe, 14.9% for Ni and 4.5% of W was presented to the best catalytic activity to RDH and a overpotential to -135 mA cm-2 of -142 mV. The XPS analysis showed that for alloys Fe-Ni-W deposited in the base occurs deposition of W (0), and the alloys Fe-Ni-Mo the ions molybdenum are reduced first to a mixture of oxides of molybdenum (IV ) and (V), forming an intermediary, which is thereafter reduced to Mo in metallic alloys. The analysis of AA alloys showed that the Fe-Ni-Mo electrodeposited in acidic environment have increased thickness which alloys in the base, being Fe-Ni-Mo obtained in acidic average thickness of 28.5 m to alloy Fe-Ni-Mo , and a thickness average of 13.3 m in the basics.
Keywords: Eletrodeposição; Ligas metálicas; Óxido de tungstênio; Óxido de molibdênio; CIENCIAS EXATAS E DA TERRA::QUIMICA